Finance and Development, June 1988. (Finance and Development; Finance and Development ;, 1988)
This paper presents the views of Michel Camdessus, Managing Director of the IMF, on how the IMF can face new challenges. Camdessus believes that the key responsibility for resolving debt difficulties lies with the indebted countries themselves. They need to be more resolute in adopting and implementing sound macroeconomic policies and bold structural reforms. Camdessus states that the IMF has available USD 12 billion to support adjustment in the low-income countries through the structural adjustment facility and the enhanced structural adjustment facility.